(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2018)
The Palaeogene deposits in the Swiss Molasse Basin, the intermediate Swiss Jura and the adjacent southern Upper Rhine Graben represent an excellent case study for interbasinal sedimentary and palaeogeographic relationships. The topographic and geologic complexity of the area led to an accumulation of local stratigraphic terms during nearly 200 years of research activity, necessitating a simplification of the lithostratigraphic framework. Additionally, the extension of the investigated area over two historically shifting language areas and the absence of a standardised supraregional lithostratigraphy adds to complexity of the situation. In revising and grouping around 200 multilingual Palaeogene lithostratigraphic terms and spellings from the northern Jura and the southern Upper Rhine Graben that accumulated since 1821 we propose a concise standardised framework of 10 formations (6 new and/or emended) and 6 new members. It avoids the confusing multitude of historic “formation” names and stratigraphic ambiguity like the “Septarienton”, “Molasse alsacienne” or the “Cyrenenmergel”. The new formations include the Turckheim Formation (formerly “Steingang”, “Conglomérats côtiers”), the Rossemaison Formation (formerly “Terre jaune”, “Gelberde”), the Pulversheim Formation (formerly “Melettaschichten”) and the Wahlebach Formation (formerly “Cyrenenmergel”, partim “Molasse alsacienne”). The Wallau and Hochberg subformations are emended and elevated to formation status. For all discussed units except the Sidérolithique new reference and/or type sections are provided and illustrated. This new framework is put in context to recent stratigraphic schemes from adjacent areas in the Upper Rhine Graben, proposing status changes and emendations for existing units (e.g. Wallau-Subformation emended to Wallau Formation). To illustrate the former complexity and the proposed standardisation in the larger area, we applied the lithostratigraphic context to 9 palaeogeographic maps. New heavy mineral data from the Delémont Basin complements the scarce regional information and is discussed in relation to Palaeogene tectonosedimentary context of the North Alpine Foreland Basin and the southern Upper Rhine Graben.